Konsep E-Commerce Dalam Penguatan Daya Saing Usaha Melalui Startup - Nurhaida, T (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
The background of the problem on the research is that the rapid advancement of technology as well as the large number of Internet users in Indonesia creates opportunities for the business world this is also supported and encouraged by the government program so that many business actors who use e-commerce to continue to be able to compete in the midst of technological development. The method used in this study is a comparative or comparative method using a qualitative descriptive nature approach by conducting in-depth interviews supported by a documentation study on the part of the GPS Medan company and the consumers of the Medan GPS company. The results of the study show that the application of e-commerce through GPS Medan startups is capable of increasing market share, improving the ability to innovate as well as facilitating consumer transactions so as to increase the competitiveness of GPS Medan enterprises. In addition, the motive driving entrepreneurs to implement e-commerce through startups is that the enterprises will be more trustworthy and increase credibility, startup businesses also do not need offices which strategically do not even need offices, increase the market share, and can build a positive branding and implementation amount for the company, as well as a strong identity. consumers, increase sales and revenue by up to twofold, help create jobs, and be able to opportunistically add new business services as a result of understanding and mastering technology.